Scientific opportunities in resilience research for cardiovascular health and wellness. Report from a National Heart, Lung, and Blood Institute workshop. Issue 12 (2nd November 2022) - Taylor, Herman A.; Finkel, Toren; Gao, Yunling; Ballinger, Scott W.; Campo, Rebecca; Chen, Rong; Chen, Shu Hui; Davidson, Karina; Iruela‐Arispe, M. Luisa; Jaquish, Cashell; LeBrasseur, Nathan K.; Odden, Michelle C.; et al.
Abstract: Exposure of biological systems to acute or chronic insults triggers a host of molecular and physiological responses to either tolerate, adapt, or fully restore homeostasis; these responses constitute the hallmarks of resilience. Given the many facets, dimensions, and discipline‐specific focus, gaining a shared understanding of "resilience" has been identified as a priority for supporting advances in cardiovascular health. This report is based on the working definition: " Resilience is the ability of living systems to successfully maintain or return to homeostasis in response to physical, molecular, individual, social, societal, or environmental stressors or challenges, " developed after considering many factors contributing to cardiovascular resilience through deliberations of multidisciplinary experts convened by the National Heart, Lung, and Blood Institute during a workshop entitled: " Enhancing Resilience for Cardiovascular Health and Wellness." Some of the main emerging themes that support the possibility of enhancing resilience for cardiovascular health include optimal energy management and substrate diversity, a robust immune system that safeguards tissue homeostasis, and social and community support. The report also highlights existing research challenges, along with immediate and long‐term opportunities for resilience research. Certain immediate opportunities identified are based on leveraging existing high‐dimensional data from longitudinal clinical studies to identify vascular resilience measures, create a 'resilience index, ' and adopt a life‐course approach. Long‐term opportunities include developing quantitative cell/organ/system/community models to identify resilience factors and mechanisms at these various levels, designing experimental and clinical interventions that specifically assess resilience, adopting global sharing of resilience‐related data, and cross‐domain training of next‐generation researchers in this field.